Yoga Reduces Body Shape Dissatisfaction Among Young Adults - Lians, Airine Stefanie; Handayani, Maria Dara Novi; Dewi, Angela Shinta; Lilis, Lilis (Althea Medical Journal, 2025)
Background: Body shape dissatisfaction is frequently experienced by young adults and may negatively impact mental well-being.  Yoga is increasingly recognized as a non-pharmacological intervention to support body image and self-acceptance. This study aimed to assess the effectiveness of yoga in reducing body shape dissatisfaction among young adults.Methods: A pre-post experimental study was conducted in 2022 among young adults experiencing body shapes dissatisfaction, selected through purposive sampling. The Body Shape Questionnaire-34 (BSQ-34) was used to measure dissatisfaction, with a total score >80 indicating dissatisfaction. Participants were randomly assigned to a yoga intervention group or a control group. The intervention group practiced Yoga Asana (posture) and Pranayama (breathing) three times per week for ten weeks via online sessions.  The BSQ-34 was distributed before and after intervention. Data were analyzed using paired t-test and SPSS version 22.0. Results: A total of 477 participants from a faculty of medicine in Jakarta, Indonesia were included; 45.3% were identified as dissatisfied with their body shape. In the yoga group, the BSQ-34 score significantly decreased after the intervention (p <0.05), indicating reduced dissatisfaction. In contrast, the control group showed a slight increase in average BSQ-34 score.Conclusions: Practicing Yoga Asana and Pranayama significantly reduce body shape dissatisfaction among young adults. Therefore, yoga may serve as a healthy choice that helps improve body image and overall mental well-being in young adults.